2006
DOI: 10.1534/genetics.105.044586
|View full text |Cite
|
Sign up to set email alerts
|

Association Mapping of Kernel Size and Milling Quality in Wheat (Triticum aestivum L.) Cultivars

Abstract: Association mapping is a method for detection of gene effects based on linkage disequilibrium (LD) that complements QTL analysis in the development of tools for molecular plant breeding. In this study, association mapping was performed on a selected sample of 95 cultivars of soft winter wheat. Population structure was estimated on the basis of 36 unlinked simple-sequence repeat (SSR) markers. The extent of LD was estimated on chromosomes 2D and part of 5A, relative to the LD observed among unlinked markers. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
802
11
15

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 923 publications
(864 citation statements)
references
References 51 publications
36
802
11
15
Order By: Relevance
“…This approach is somewhat similar to the method implemented by Breseghello and Sorrells (2006), even though they have removed only very similar haplotypes and in the current study only distant haplotypes were selected. Taking into account that T. dicoccoides is a selfer, LD decay in Lr10 was very rapid, within 1-2 kb.…”
Section: Lr10 Diversity Within and Between Populationsmentioning
confidence: 99%
“…This approach is somewhat similar to the method implemented by Breseghello and Sorrells (2006), even though they have removed only very similar haplotypes and in the current study only distant haplotypes were selected. Taking into account that T. dicoccoides is a selfer, LD decay in Lr10 was very rapid, within 1-2 kb.…”
Section: Lr10 Diversity Within and Between Populationsmentioning
confidence: 99%
“…However, some components such as TGW are characterized by a higher heritability than grain yield itself (Bezant et al, 1997;Huang et al, 2006;Tsilo et al, 2010;Deng et al, 2011). TGW is positively correlated with agronomic yield (Baril 1992;Fuller, 2007;Maccaferri et al, 2011) and flour yield (Chasten et al, 1995;Breseghello and Sorrells, 2006;Williams et al, 2013). Moreover, the high heritability values (59% to 96%) in most of the cultivars studied so far have proved that this character is phenotypically the most-stable yield component (Giura and Saulescu, 1996;Huang et al, 2006;Sun et al, 2009;Tsilo et al, 2010;Patil et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While, grain shape is generally estimated by length, width, vertical perimeter, sphericity and horizontal axes proportion (Breseghello and Sorrells, 2007). Many studies have been shown that wheat grain size and shape is positively correlated with TGW and they have affected flour yield, end-use quality and market price (Evers et al, 1990;Breseghello and Sorrells, 2006;Tsilo et al, 2010;Cui et al, 2011;Blanco et al, 2012;Williams et al, 2013;Rasheed et al, 2014). Theoretical models predict that milling yield could be increased by optimizing grain size and shape with large and spherical grains being the optimum grain morphology (Evers et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…It has successfully been used to detect quantitative trait loci (QTL) for agronomically important traits in many crop species including maize (for example, Harjes et al, 2008), wheat (for example, Breseghello and Sorrells, 2006;Reif et al, 2011a, b), barley (for example, Wang et al, 2012;Berger et al, 2013) and rice (for example, Huang et al, 2010). Traditional approaches for QTL detection in plants are based on linkage mapping in bi-parental populations.…”
Section: Introductionmentioning
confidence: 99%